A strategy for a competitive Europe: Boosting R&D, unleashing investment, and reducing regulatory burdens - Andrea Dugo; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2024)
The EU stands at a crucial economic juncture. Economic growth in Europe's mature economies has stagnated, with productivity and other indicators of economic vitality showing poor results. Public debt is alarmingly high in several countries, and the region faces new fiscal demands due to an ageing population, conflicts and war, and the energy transition. To reverse its economic decline, Europe must adopt a new strategy for improved competitiveness. The starting point of this strategy should be an honest assessment of Europe's declining productivity compared to leading economies like the US. Historically, some European countries matched or even surpassed US productivity levels, but this gap has widened over the past three decades. While the US economy has also faced challenges, its technology, R&D, and innovation sectors have significantly boosted productivity growth. This paper identifies three key areas for policy improvement to rejuvenate Europe's economic dynamism. By addressing these areas, Europe can create a more favourable environment for business growth, innovation, and long-term economic stability.
Keywords: 330